A proper reference metabolic equivalent value to assess physical activity intensity in Japanese female nurses - Yuki Ideno; Kunihiko Hayashi; Jung Su Lee; Yukiko Miyazaki; Shosuke Suzuki (BMC, 2019)
Abstract Background Various questionnaires have been developed to assess physical activity, but only a few simple questionnaires are suitable for self-administration in large groups of midlife working women. This study examined the usefulness of the Japan Nurses' Health Study (JNHS) questionnaire for self-administered physical activity surveys. Methods The JNHS physical activity questionnaire consisted of items covering seven degrees of intensity. The metabolic equivalents (METs) for the physical activity intensity of the questionnaire were estimated from energy expenditure as measured by a uniaxial accelerometer with the Markov Chain Monte Carlo (MCMC) simulation. The estimated METs were then assigned to the JNHS baseline survey data, and the total energy expenditure (TEE) and the time spent performing ≥3 METs hour of physical activity, called moderate to vigorous intensity physical activity (MVPA), were calculated. Results For working situations, application of the MCMC simulation resulted in estimated reference values of 1.2 METs for "sitting work", 1.6 METs for "standing work", 1.8 METs for "walking work", and 4.5 METs for "heavy work". For non-working situations, the estimated values were 1.1 METs for sedentary time, 2.4 METs for "moderate physical activity", 4.4 METs for "vigorous physical activity", and 9.4 METs for "very vigorous physical activity". When these estimated METs were used, the mean TEE/day was 1808 kcal. This corresponded to − 3.0% of the TEE/day generated by the accelerometer. These estimated MET values showed similar results as a previous study measuring activity using the doubly-labeled water method. The number of hours per week of MVPA significantly decreased with age, which is also consistent with previous findings. Conclusions Estimated reference MET values in this study were similar to those in previous studies of Japanese women. The JNHS questionnaire is therefore useful for epidemiological surveys of midlife working women because it assigns estimated MET values as physical activity intensities.